Prevalence of the Absence of the Palmaris Longus and Functional Flexor Digitorum Superficialis of the Little Finger in the Indian Population - Rajendiran, Subashini; Rajappa, Srinivasan; Jaichandran, Sandhiya; Bhat, Anil; Thatte, Mukund (Indian Journal of Plastic Surgery, 2024)
Background The absence of the palmaris longus (PL) varies with race. The presence of a functional flexor digitorum superficialis (FDS) of the little finger also varies widely. The aim of this study is to determine the prevalence of the absence of the PL and functional FDS of the little finger in the Indian population.Materials and Methods This is a prospective observational study conducted as a part of the Indian normative data project of the Indian Society for Surgery of the Hand. The presence of the PL was assessed by Schaeffer's test. The function of the FDS was assessed by the standard test and modified test and its function designated as absent, present independently, or present combinedly with the ring finger FDS.Results A total of 200 volunteers including 84 males and 116 females in the 21- to 60-year age group were examined. Of the 400 hands examined, the PL was absent in 26 upper limbs (6.5%). The PL was absent unilaterally in 12 individuals (6%) and bilaterally in 7 individuals (3.5%). Of the 400 little fingers examined, FDS function was absent in 72 fingers (18%), while 67 fingers (16.75%) had a common function and 261 fingers (65.25%) had an independent function. Only 2% had a bilateral absence of both the PL and functional FDS tendons and 5% had a unilateral absence of both tendons.Conclusion The PL and FDS of the little finger were more absent in the right side than in the left side, but the difference was not statistically significant. There was no significant association between the absence of the PL and the absence of the functional FDS of the little finger.
Keywords: tendon absence; palmaris longus; flexor digitorum superficialis absence; Schaeffer's test; Baker's test; normative data